Profiling of headspace volatiles from Escherichia coli cultures using silicone‐based sorptive media and thermal desorption GC–MS. Issue 22 (5th November 2018) - Devaraj, Harish; Pook, Chris; Swift, Simon; Aw, Kean C.; McDaid, Andrew J.
Abstract: Headspace sorptive extraction technique using silicone based sorptive media coated stir bars is used for the first time here to extract, identify, and quantify heavy volatile organic compounds present in Escherichia coli culture headspace. Detection of infection presence is largely accomplished in laboratories through physical sampling and subsequent growth of cultures for biochemical testing. The use of volatile biomarkers released from pathogens as indicators for pathogenic presence can vastly reduce the time needed whilst improving the success rates for infection detection. To validate this, by using a contactless headspace sorptive extraction technique, the volatile compounds released from E. coli, grown in vitro, have been extracted and identified. Two different sorptive media for extracting these headspace volatiles were compared in this study and the identified volatiles were quantified. The large phase volume and wider retention of this sorptive technique compared to traditional sampling approach enabled preconcentration and collection of wider range of volatiles towards developing an extensive database of such heavy volatiles associated with E. coli . This supplements the existing data of potential bacterial markers and use of internal standards in these tests allows semi‐quantitative estimation of these compounds towards the development and optimization of novel pathogen sensing devices.